An Analysis of Effect on Energy Saving of Trucks in Transport and Logistics Business - Poolkrajang, Akkarat (International Journal of Energy Economics and Policy, 2023)
This research aimed to analyze the effect on energy saving of trucks in the transport and logistics business by monitoring and evaluating truck drivers. A sample of seventy-four 10-wheel trucks was selected. Fuel consumption data was collected from drivers as they operated their vehicles using GPS systems. The results suggested a total reduction of fuel consumption with improved fuel consumption rates. Annual mileage affected better energy saving: trucks with high annual mileage were more capable of reducing fuel consumption than those with low mileage. The effect on energy-saving was 0.16 ktoe per year, suggesting a cost saving of 5.8 million baht per year.